2016
DOI: 10.3892/mmr.2016.5807
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is involved in aldosterone-induced mesangial cell proliferation

Abstract: The aim of the present study was to investigate whether autophagy is involved in aldosterone (Aldo)-induced mesangial cell (MC) proliferation. MCs were incubated with 10−7 M Aldo for 24 h. Proliferation of MCs, and the underlying mechanisms, were subsequently analyzed using [3H]thymidine assay, cell counting assay, western blotting and RNA interference (RNAi). Aldo was revealed to induce autophagy, as indicated by the increased conversion from microtubule-associated protein 1A/1B-light chain 3 (LC3)-I to LC3-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Autophagy is known to be a self-degradative process that is important for balancing sources of energy at critical times during development, and in response to nutrient stress ( 32 ). Studies have demonstrated that autophagy is involved in a number of general processes, including proliferation, development, apoptosis and cell death ( 33 , 34 ). LC3BII, Beclin1 and P62 are closely associated with the formation of autophagosomes, serving as markers of autophagy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is known to be a self-degradative process that is important for balancing sources of energy at critical times during development, and in response to nutrient stress ( 32 ). Studies have demonstrated that autophagy is involved in a number of general processes, including proliferation, development, apoptosis and cell death ( 33 , 34 ). LC3BII, Beclin1 and P62 are closely associated with the formation of autophagosomes, serving as markers of autophagy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with the fact that the site of contact of mitochondria with the endoplasmic reticulum induced the formation of autophagosomes. 54 Autophagy is a self-protective cellular mechanism limiting toxicity to promote cell survival, 55,56 and autophagy could control inflammatory signaling by regulating the secretion of inflammatory mediators. 57,58 Evidence indicates that autophagy is closely related to the inflammatory response, 59 which is consistent with our findings that DEHPexposed quail had increased levels of TNF-α and the formation of typical autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of PI3K/Akt signaling inhibits the phosphorylation of mTOR, thereby enhancing autophagy ( Wang et al, 2015 ). Besides, autophagy can also be induced by RAS/RAF/MEK/ERK signaling pathway ( Zhang et al, 2017 ; Sooro et al, 2018 ) and aldosterone ( Yang et al, 2016 ; Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Chen et al, 2015 ; Chen and Sun 2019 ). Aldosterone may induce autophagy to cause an aggravation of diseases ( Yang et al, 2016 ; Luo et al, 2017 ), and KL (+/-) mice showed elevated serum levels of aldosterone. These results suggest that Klotho deficiency may decrease elastin levels in smooth muscle cells by upregulating aldosterone and thereby inducing autophagy ( Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%